The Effect of Customer Relationship Management and Service Quality to Customer Loyalty on Indihome Customers PT Telkom Indonesia Regional IV Semarang City Area - Mahastu Winengku Kinasih; Riyadi - Riyadi; Nanang Adie Setyawan (Politeknik Negeri Semarang, 2021)
The purpose of this research to analyze the effect of customer relationship management and service quality on customer loyalty to IndiHome on customers of PT Telkom Indonesia Regional IV Semarang City Region. The data collection method used is a questionnaire and documentation using a measurement scale semantic differensial and the sample collection method is incidental sampling of 100 respondents. The types of data used in this study are primary data and secondary data. The data analysis model used is multiple linear regression. The data analysis technique for hypothesis testing uses the F test, t test and R2 test with IBM SPSS 23 analysis tool which shows that the regression equation Y = 0.372X1 + 0.427X2. Based on the test results the coefficient of determination is 54.8% while the remaining 45.2% is influenced by other factors that are not included in this study. The results of this study can be concluded that customer relationship management and service quality have a positive and significant influence on customer loyalty.